2023
DOI: 10.1097/jpa.0000000000000480
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Research: A National Survey of Physician Assistant Faculty

Abstract: IntroductionSuccess in research is a well-known challenge for physician assistant (PA) educators. Multiple barriers to research productivity have been proposed. This study examines potential barriers to PA research productivity.MethodsTwo hundred forty-seven PA programs were stratified by region and Carnegie classification, creating 28 strata. One program was randomly sampled from each stratum, and faculty from sampled programs were invited to participate (N = 214). An electronic survey was deployed via Qualtr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(15 citation statements)
references
References 30 publications
0
14
1
Order By: Relevance
“…This project received exempt status from the local institutional review board and is a subset analysis of a previously published cross-sectional study. 4…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…This project received exempt status from the local institutional review board and is a subset analysis of a previously published cross-sectional study. 4…”
Section: Methodsmentioning
confidence: 99%
“…Multiple barriers to PA research productivity have been suggested 2,3 ; a recent study found that lack of interest and lack of engagement with mentors by PA educators were underreported barriers. 4 Gender disparities in advancement in rank, representation in leadership, and salary are well-researched in other professions, [5][6][7] but nascent in the PA profession. 8,9 Gender differences in scholarly output exist in other professions, 6,[10][11][12] but are less wellunderstood in the PA profession.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations